How U.S. Conservatives perceive and respond to international nutrition issues, and how to shape messaging for successful advocacy - Jennifer Eaton Dyer; Brian Lloyd Heuser (Health for All Nations, 2018)
Since 1990, tremendous strides have been made in global health and development toward achieving the Millennium Development Goals. With a united front of forces, including governments, coalitions, private sector, foundations, philanthropic organizations, and the faith community, millions of lives have been saved from extreme poverty and disease. Yet, some issues enjoy more robust funding and notoriety than others. For instance, AIDS, tuberculosis, and malaria enjoy the majority of the U.S. foreign assistance funding in global health. Nutrition, notably, has remained stagnant for decades. Through this research, we sought to test the appetite for increased funding for international nutrition and food security issues among Political, Religious, Social Conservatives (PRSCs), and the General Population (GP) to gauge perception and response to the issue and its correlates. Our objective with these national surveys was to understand the best choice of language to promote awareness, education, and prompt advocacy for global nutrition and food security issues. With this research, we found that conservatives were motivated by national security issues first and at a macro-level, not their faith, finances or moral foundation. We recommend that education be enhanced among conservatives regarding U.S. foreign assistance, nutrition funding and implementation, and nutrition-related terminology, including stunting, wasting, and anemia. Moreover, we recommend communicating strong narratives about mothers, children, and infants, particularly a child's first 1,000 days, from conception to two years, which has proved to elicit the most positive response among all messaging.